Circular - Garratt, G. T.
1938-02-04 038-0162-001 BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: MISS BETTY L. ARNE 53, MARSHAM STREET LONDON, S.W.1. TELEPHONE: VICTORIA 2168 4th February, 1938. Dear Sir or Madam, We are writing to you as one who has given us generous support in our appeal for the Basque children saved from Bilbao. We feel the time has come to give you an account of this epic of relief work, of how it has been carried out and of the position to-day. You will remember - who can forget it? - the wave of horror produced by the destruction of Guernica from the air and the massacre which attended it. You will remember the impassioned appeals to rescue the children of Bilbao which immediately began to reach us. You will remember how the whole of this country was stirred by the movement to bring the children here; how our own doctors went out to pick the children, being forced to carry on their work at night by the daily air raids; how the parents beseiged our representatives begging them to rescue the children; how at last we brought away the Habana crowded to overflowing by these innocent sufferers of the war. We brought 3,826; and in the camp at Stoneham, a miracle of successful organisation, we began the care of the children, began to nurse them back to health and happiness. Gradually they were drafted away to homes in all parts of the country. We had given the National Government an undertaking that there would be no individual adoptions, no cost to public funds and no question of the children remaining permanently in this country - all were to be returned to their parents when conditions permitted. So the children were divided up among more than a hundred homes. In many places local committees undertook the complete care of the children for us; they have done wonders in maintaining their support. Perhaps one of the most moving details of the work has been the eager and self-sacrificing help given by the people of the distressed areas, South Wales and Durham in particular. 292/946/38/162(I)